4 - EUROPE-AFRICA ECONOMIC RELATIONS WITHIN THE FRAMEWORK OF THE LOME CONVENTION: NEO COLONIALISM OR NEW INTERNATIONAL ECONOMIC ORDER - MARTIN, GUY (Africa Development, 1979)
The Lome Convention, signed on February 28,1975 between the 9 countries of the European Communities and 46 countries of Africa, the Caribbean and the Pacific as a sequel to Yaounde I (1964-69) and Yaounde II (1971-75) has been hailed as a landmark in the emerging New International Economic Order. This paper, through a cursory study of the main characteristics and innovative features of this Convention, attempts to assess the validity of this view. More specifically, an effort is made at evaluating the Convention in the light of the New Interna tional Economic Order, as well as with respect to the theory of « neocolonialism » in order to determine which of these views the Convention better typifies. The main concern of this work is to determine whether, and to what extent, the Con vention is beneficial to the economic development of the African countries con cerned.